TINJAUAN YURIDIS SOSIOLOGIS TINDAK PIDANA NARKOTIKA DALAM PENYIDIKAN DI SAT RESNARKOBA POLRES BOYOLALI - JALU W., TRI (Dinamika Hukum, 2016)
The purpose of thisresearchis to study and analyze the criminal act ofnarkotics and the steps of investigation performance on the criminal act ofnarkotics in the investigation in Sat Resnarkoba Polres Boyolali (Resort Unit ofNarcotics and Drugs, Boyolali Police) .Background. The provisions of a law which regulates the matter ofNarcotics had been made and implemented, nevertheless, crime related toNarcotics has not been able to be reduced. In many cases, there were manycroupiers and sellers of narcotics and drugs who were arrested and got a heavysanction, but, other perpetrators seemed not to care, even the provisions of thelaws governing the Narcotics issue have been compiled and enforced, but narcoticcrimes can not be eradicated thoroughly.The Writer conducted a preliminary research awal in the form of collectingthe supporting researched data. After that, the Writer conducted aresearchin SatReserse Narkoba Polres Boyolali. The techniques of data collection are in theforms of interview and documentation study. All data collected either primary orsecondary data would be analyzed qualitatively that was explanation according tothe quality, which prevailed on fact as being in line with the primary data whichwas related to the theories in the secondary data.Discussion. That the act of the suspect REJO AHMADY Bin AHMADTARMUJI, Place and Date of Birth: Boyolali, 17 August 1971, Age: 44 y.o.,Religion: Islam, Gender: Male, Occupation: Private Worker (motorcycleworkshop), Last Education: Elementary School graduated in 1986, Address: Dk.Cepogo Rt 03 Rw 01 Ds. Cepogo Kec. Cepogo Kab. Boyolali, had broken the lawand had met the elementes of criminal act of Narcotics misuse as meant on theformulation: Article 112 paragraph (1) jo article 114 paragraph (1) jo article 127paragraph (1) Actnumber 35 of 2009 concerning Narcotics. The Steps of TheInvestigation Completion Process of The Criminal Act were: 1. Arranging aPolice Report, 2. Composing a Task Command Letter, 3. Composing anInvestigation Command Letter, 4. Information on The Beginning of Investigation,5. Composing an Appointment of Lawyer, 6. Composing a Rejection on theLawyer, 7. Composing a Statement Letter, 8. Composing an Arrest CommandLetter, 9. Composing a Detention Command Letter, 10. Composing a SearchingCommand Letter, 11. Composing a Confiscation Command Letter, 12. Examiningthe Evidences in Laboratory.Keywords: Criminal act of narcotics, Investigation